Influence of Typhoons on Chemical Makeup of Rainwater in Zhanjiang, China - Zhen Zeng; Xin Zhou; Zhiyang Li; Fajin Chen; Huijie Luo; Guirong He; Ziyun Deng; Chunqing Chen; Qibin Lao (Aerosol and Air Quality Research)
Abstract Typhoons are extreme weather events with substantial effects on ambient air. However, whether typhoons of different intensities have the same effects on the chemical composition of rainwater is unclear. Therefore, 4 years of rainwater sampling and an analysis of the ionic composition (Cl−, Ca2+, Na+, SO4 2–, Mg2+, F−, and K+) of rainwater were conducted in Zhanjiang, a city on the southern tip of mainland China. The ionic composition varied seasonally, being high in dry seasons whereas low in wet seasons; ion levels were controlled by rainfall dilution effects rather than by the monsoon transition. Source determination demonstrated that the marine influences in the dry and wet seasons were similar, further indicating the limited impact of the monsoon climate on the ionic species’ seasonal patterns. The heavy rain and strong wind (> 47.4 m s−1) brought by a super typhoon led to an increase in ionic species carried from continental sources into ambient air, and such species were then captured by precipitation. The weak winds (10.71– 12.84 m s−1) brought by weak typhoons failed to blow such ions into the air, but rainfall dilution still occurred and was dependent upon rainfall amount. Our results suggest that strong typhoons can increase ion concentrations in rainwater, whereas weak typhoons reduce such concentrations. The results provide new insight into the relationship between air quality and typhoons.